Is a clinician’s personal history of domestic violence associated with their clinical care of patients: a cross-sectional study - Cathy Humphreys; Elizabeth McLindon; Kelsey Hegarty (BMJ Open, 2019)
Objective To investigate whether domestic violence (DV) impacts on health professionals’ clinical care of DV survivor patients.Design, setting Descriptive, cross-sectional study at an Australian tertiary maternity hospital.Participants 471 participating female health professionals (45.0% response rate).Outcome measures Using logistic and linear regression, we examined whether health professionals’ exposure to lifetime DV was associated with their clinical care on specific measures of training, attitudes, identification and intervention.Results DV survivor health professionals report greater preparedness to intervene with survivor patients in a way that is consistent with ideal clinical care. This indicates that personal DV experience is not a barrier, and may be a facilitator, to clinical care of survivor patients.Conclusions Health professionals are at the front line of identifying and responding to patients who have experienced DV. These findings provide evidence that survivor health professionals may be a strength to the healthcare organisations in which they work since among the participants in this study, they appear to be doing more of the work seen as better clinical care of survivor patients. We discuss the need for greater workplace supports aimed at promoting safety and recovery from violence and strengthening clinical practice with patients.